Development of Novel Topical Cosmeceutical Formulations from Nigella sativa L. with Antimicrobial Activity against Acne-Causing Microorganisms - Nirmani Wishwakala Nawarathne; Kanchana Wijesekera; Weerasinghe Mudiyanselage Dilip Gaya Bandara Wijayaratne; Mayuri Napagoda (The Scientific World Journal)
Acne vulgaris occurs due to the inflammation of sebaceous follicles in the skin. It is triggered by the activity of some bacterial species like Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. Acquisition of antibiotic resistance by these microorganisms and adverse effects associated with the current treatment regimens necessitate the introduction of novel therapeutic agents for acne vulgaris. Thus, this study was undertaken to develop novel gel formulations from seeds of Nigella sativa L. and to evaluate the antibacterial potential against some acne-causing bacterial species. The antibacterial activity of seed extracts was initially screened against S. aureus and P. acnes by the agar well diffusion method. Thereafter, topical gels were formulated incorporating the ethyl acetate extract of seeds of N. sativa at three different concentrations. These topical formulations were subjected to antimicrobial activity studies while the stability was evaluated over a period of 30 days. All three formulations were capable of inhibiting the growth of S. aureus and P. acnes, with the highest antibacterial activity in the formulation comprising 15% of the seed extract. Interestingly, the antibacterial potency of this formulation against S. aureus surpassed the commercial synthetic product used as the positive control. Moreover, any alteration in color, odor, homogeneity, washability, consistency, and pH was not observed while the antibacterial potency was also retained during the storage period. The potent antibacterial activity in topical gel formulations developed from the ethyl acetate extract of N. sativa signposts their suitability as alternatives to existing antiacne agents in the management of acne vulgaris.